2019
DOI: 10.1371/journal.pntd.0007537
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ligase TRIM56 is a host restriction factor of Zika virus and depends on its RNA-binding activity but not miRNA regulation, for antiviral function

Abstract: Infection by Zika virus (ZIKV) is linked to microcephaly and other neurological disorders, posing a significant health threat. Innate immunity is the first line of defense against invading pathogens, but relatively little is understood regarding host intrinsic mechanisms that guard against ZIKV. Here, we show that host tripartite motif-containing protein 56 (TRIM56) poses a barrier to ZIKV infection in cells of neural, epithelial and fibroblast origins. Overexpression of TRIM56, but not an E3 ligase-dead mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…In the case of Zika virus (ZIKV) infection, TRIM56 can indeed identify and capture vRNA [45]. Restriction of ZIKV by TRIM56 depended on an intact C-terminal region as well as its E3 ligase activity signifying, in contrast to what was observed with IAV, that TRIM56 may recognize vRNA and utilize its E3 ligase activity to prevent ZIKV replication through an as yet unresolved mechanism [45]. Viral restriction that is independent of a TRIM's E3 ubiquitin ligase function was recently described for TRIM25 [46].…”
Section: Proteasome-independent Antiviral Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Zika virus (ZIKV) infection, TRIM56 can indeed identify and capture vRNA [45]. Restriction of ZIKV by TRIM56 depended on an intact C-terminal region as well as its E3 ligase activity signifying, in contrast to what was observed with IAV, that TRIM56 may recognize vRNA and utilize its E3 ligase activity to prevent ZIKV replication through an as yet unresolved mechanism [45]. Viral restriction that is independent of a TRIM's E3 ubiquitin ligase function was recently described for TRIM25 [46].…”
Section: Proteasome-independent Antiviral Mechanismsmentioning
confidence: 99%
“…Although the exact mechanism of restriction is unclear, this hypothesis is plausible as the C terminus of TRIM56 was found to have high sequence homology to the positively charged surfaces in NHL repeats, which would afford a means to interact with the negatively charged sugar phosphate backbone of vRNA () [44]. In the case of Zika virus (ZIKV) infection, TRIM56 can indeed identify and capture vRNA [45]. Restriction of ZIKV by TRIM56 depended on an intact C-terminal region as well as its E3 ligase activity signifying, in contrast to what was observed with IAV, that TRIM56 may recognize vRNA and utilize its E3 ligase activity to prevent ZIKV replication through an as yet unresolved mechanism [45].…”
Section: Direct Antiviral Roles Of Trimsmentioning
confidence: 99%
“…Consistent with previous researches, recent studies have shown that carboxy-terminal domains of TRIM56 inhibit IAV and Influenza B virus (IBV) replication by blocking viral RNA synthesis ( Liu et al, 2016a ). Similarly, TRIM56 could also be a host restriction factor of the Zika virus, depending on its RNA-binding activity ( Yang et al, 2019 ). TRIM22 can restrict retrovirus by interfering with viral Gag protein transport by regulating transcription factor specificity protein 1 (Sp1) (Sp1) ( Kajaste-Rudnitski et al, 2011 ; Turrini et al, 2015 ).…”
Section: Trim Proteins Play a Direct “Game” With Virusesmentioning
confidence: 99%
“…TRIM22 and TRIM41 inhibit influenza A virus infection by targeting nucleoprotein for degradation (7,8). TRIM56 suppresses Zika virus (ZIKV) replication through sequestration of its genomic RNA (9).…”
Section: Introductionmentioning
confidence: 99%